High Prevalence of Ixodidae Ticks in Dogs Across Diverse Agro-Climatic Zones of Western Maharashtra - Ranjeet Mhaisekar, Nirja; Dhanaji Pawar, Prashant; Madhavrao Chigure, Gajanan; Gajanan Nimbalkar, Vidya; Harihar Belsare, Bhagyashri; Das Singla, Lachhman (Indian Journal of Veterinary Sciences and Biotechnology, 2025)
This research work highlights the alarming prevalence of Ixodidae ticks infesting dogs across four distinct agro-climatic zones of Western Maharashtra. A total of 220 dogs were screened, resulting in 100 tick samples identified through rigorous methods. Findings revealed a concerning overall prevalence of 45.5% (100/220) of Ixodid ticks in the region, with Rhipicephalus sanguineus as the predominant species, comprising 53% (53/100) of the samples. Remarkably, dogs aged 1 to 3 years showed the highest infestation rate at 49.4% (38/77). Male dogs were disproportionately affected, with a prevalence of 52% (53/102). Stray dogs emerged as particularly vulnerable hosts, exhibiting an alarming infestation rate of 57.4% (39/68). Among breeds, the Greyhound demonstrated the highest prevalence at 63.3% (19/30). Moreover, skinny dogs faced the most significant tick burden, with a striking 70% (7/10) infestation rate. The ear was identified as the most common attachment site for ticks, accounting for 43% (43/100) of occurrences. This comprehensive study emphasizes the urgent need for targeted interventions to combat tick infestations in dogs across Western Maharashtra.
Keywords: Ixodidae; Rhipicephalus sanguineus; Tick prevalence; Western Maharashtra